Podnikatelský záměr-rozšíření prodejní sítě - Dvorský, Jakub (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Cílem diplomové práce je zpracovat podnikatelský záměr pro firmu Vodoplast, která by chtěla v blízké době otevřít svoji maloobchodní prodejnu instalatérského materiálu a sanitární techniky v městě Zábřeh. Práce by se měla stát důležitým zdrojem informací vedoucích k úspěšné realizaci.

The aim of the dissertation is to prepare a business plan for the company called Vodoplast, situated in Zábřeh, which wants to open its retail store of plumbing materials and sanitary equipment at any time. The dissertation should become an important source of information leading to successful realization.
Business Plan-Extension of Sales Network
Keywords: Podnik; podnikání; podnikatel; podnikatelský plán; analýza trhu; analýza zákazníků; analýza konkurence; marketingový plán; PEST analýza; SWOT analýza; organizační plán; finanční plán; bod zvratu; hodnocení rizik.; Company; business; businessman; business plan; market analysis; consumer analysis; analysis of competition; marketing plan; PEST analysis; SWOT analysis; organizational plan; financial plan; break-even point; risk assesment.